Effectiveness of Fascial Manipulation Method (FM®) - Podstawka, Zuzanna; Pińkowska, Oliwia; Byś, Aleksandra; Gawda, Piotr (Journal of Education, Health and Sport, 2020)
Background Fascial Manipulation® (FM®) is a manual method of treatment created by Luigi Stecco that centres on the muscular fascia. Fascia is a fibrous collagenous tissue which, with its wide strands, connects all the connective tissues in the body into a whole. Fascia can also cause restriction of motion of the organs as a result of an injury, inflammation or infection. FM® technique bases on identification and therapy of specific points, which are located at the point of convergence of the vectorial forces of the muscles involved in every movement. The aim of this literature review was to analyze publications on the use of FM® in treatment of pain and functional dysfunctions. Materials and methods Material for this literature review was found by two independent authors using PubMed, Cochrane library, ScienceDirect and PEDro databases. In order to identify appropriate studies, a combination of keywords , fascial manipulation”, „pain”, „dysfunction” was used. Finally, 10 publications were qualified for a literature review. Results In the analyzed ten publications, improvement after treatment, reduction of pain and better functional outcome in patients conditions were figured. Six authors had some similar conclusions which state that the positive results of treatment last over time. One study presented opposite findings and state that the treatment has not brought long-lasting effects. Conclusions Considering all the reports on this subject, it is suggested that FM® therapy is worth considering in treatment of pain disorders, orthopaedic dysfunctions and postural disabilities. Further research of the subject on whether the treatment results are sustainable is necessary.